Respon dan Pengaruh Pendekatan Contextual Teaching Learning Terhadap Hasil Belajar IPA Materi Perubahan Sifat Benda Pada Siswa Kelas V Sekolah Dasar - Damar Septian; Ifa Fauziyah Farid; Selamet Syaifuddin; Sri Hastuti (Pendidikan Fisika, FKIP, Universitas Nahdlatul Ulama Cirebon, 2021)
The relationship between student context and subject matter is often emphasized in science learning. Improving student learning outcomes also always receives special attention. However, student learning outcomes still do not meet the minimum completeness criteria. The Contextual Teaching and Learning (CTL) approach is an alternative solution because the concept of learning relates the material being taught with the situations around students. This study aims to determine the students’ responses to science learning using the CTL approach and its effect on science learning outcomes, material properties and changes in the shape of objects. This research was an experimental research. The sampling technique used was saturated sampling. The research sample was the fifth grade students of SD UnggulanMuslimat NU Kudus, totaling 60 students. The independent variable was the CTL learning model while the dependent variable was the science learning outcome. The research instrument used were tests and non-tests. The results of the study were the students' responses were categorized as very strong and there was a significant effect of the CTL approach on science learning outcomes. These findings are not only to improve student learning outcomes but also provide knowledge about the benefits of science in the context of the student's environment.